Evolution of Cyber Technologies and Operations to 2035 - Blowers, Misty; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book explores the future of cyber technologies and cyber operations which will influence advances in social media, cyber security, cyber physical systems, ethics, law, media, economics, infrastructure, military operations and other elements of societal interaction in the upcoming decades. It provides a review of future disruptive technologies and innovations in cyber security. It also serves as a resource for wargame planning and provides a strategic vision of the future direction of cyber operations. It informs military strategist about the future of cyber warfare. Written by leading experts in the field, chapters explore how future technical innovations vastly increase the interconnectivity of our physical and social systems and the growing need for resiliency in this vast and dynamic cyber infrastructure. The future of social media, autonomy, stateless finance, quantum information systems, the internet of things, the dark web, space satellite operations, and global network connectivity is explored along with the transformation of the legal and ethical considerations which surround them. The international challenges of cyber alliances, capabilities, and interoperability is challenged with the growing need for new laws, international oversight, and regulation which informs cybersecurity studies. The authors have a multi-disciplinary scope arranged in a big-picture framework, allowing both deep exploration of important topics and high level understanding of the topic. Evolution of Cyber Technologies and Operations to 2035 is as an excellent reference for professionals and researchers working in the security field, or as government and military workers, economics, law and more. Students will also find this book useful as a reference guide or secondary text book.
Introduction -- Resiliency in Future Cyber Combat -- Internet of Things -- The Invisible War -- Cyber in Space -- Future Trends in Large Data Handling -- The Application of Virtual Reality for Cyber Information Visualization and Investigation -- Quantum Information Science -- Dark Web and the Rise of Underground Networks -- The Bitcoin -- The Rise of Social Media and Its Role in Future Protests and Revolutions -- Is Skynet the Answer? Rules for Autonomous Cyber Response Capabilities -- Ethical Considerations in the Cyber Domain -- Ethical Challenges of 'Disruptive Innovation' -- High School Student Visions of Disruptive Innovation.
Keywords: Computer security; Data structures (Computer scienc; Law and economics; Systems and Data Security; Data Structures and Information Theory; Law and Economics